2006
DOI: 10.1016/j.ijdevneu.2005.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid phenethyl ester (CAPE) attenuates cerebral vasospasm after experimental subarachnoidal haemorrhage by increasing brain nitric oxide levels

Abstract: Our results indicate that CAPE is effective in attenuating delayed cerebral vasoconstriction following experimental SAH. Our findings also suggest that the elevation of lipid peroxidation and reduction of NO bioavailability, resulting from the generation and the interaction of free radicals, have a significant role in the pathogenesis of vasospasm after SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 41 publications
(50 reference statements)
1
14
0
Order By: Relevance
“…57,58 Previous studies implicated that both ferulic acid and caffeic acid modulated NO pathways in the central nervous system. [59][60][61] Increased central NO had a role of restraining sympathetic outflow, 50,62,63 thereby attenuating reflex tachycardia when arterial baroreceptors were unloaded due to blood pressure reduction. 58 Although the current data on CGAs are promising, gaps in knowledge remain to be filled.…”
Section: Molecular Targets Of Chlorogenic Acid In Blood-pressure Regumentioning
confidence: 99%
“…57,58 Previous studies implicated that both ferulic acid and caffeic acid modulated NO pathways in the central nervous system. [59][60][61] Increased central NO had a role of restraining sympathetic outflow, 50,62,63 thereby attenuating reflex tachycardia when arterial baroreceptors were unloaded due to blood pressure reduction. 58 Although the current data on CGAs are promising, gaps in knowledge remain to be filled.…”
Section: Molecular Targets Of Chlorogenic Acid In Blood-pressure Regumentioning
confidence: 99%
“…Thus, the use of free radical scavengers in animal models of SAH [11,12] and some clinical trials [13,14] have demonstrated beneficial effects of these agents on ischemic neurological deficits due to SAH-induced vasospasms. We have recently shown that melatonin, which is a potent free radical scavenger, reversed SAH-induced histopathological and biochemical alterations [15].…”
Section: Introductionmentioning
confidence: 99%
“…1 It is plausible that the inflammatory response to oxidant stress represent a critical step in the pathogenesis of cerebral vasospasm (CVS) pursuant to SAH. [2][3][4] In addition, glutamate plays an important role in the pathogenesis of neuronal injury after ischemic injury. 5 Glutamate transporter-1 (GLT-1) predominates among the functional glutamate transporters, which are essential for maintaining a low extracellular glutamate concentration and for preventing glutamate neurotoxcity.…”
mentioning
confidence: 99%